2020
DOI: 10.1038/s41612-020-00149-4
|View full text |Cite
|
Sign up to set email alerts
|

Using UNSEEN trends to detect decadal changes in 100-year precipitation extremes

Abstract: Sample sizes of observed climate extremes are typically too small to reliably constrain return period estimates when there is non-stationary behaviour. To increase the historical record 100-fold, we apply the UNprecedented Simulated Extreme ENsemble (UNSEEN) approach, by pooling ensemble members and lead times from the ECMWF seasonal prediction system SEAS5. We fit the GEV distribution to the UNSEEN ensemble with a time covariate to facilitate detection of changes in 100-year precipitation values over a period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(117 citation statements)
references
References 78 publications
2
99
2
1
Order By: Relevance
“…Furthermore, convection‐permitting models are sensitive to boundary conditions from ESMs (Keller et al., 2018; Shepherd, 2014); thus understanding the mechanisms behind observed changes requires sensitivity analyses, which are still computationally unfeasible. Strategies to exploit the available model runs are thus needed to reach even a minimal level of accuracy for, say, 100‐year events (e.g., Kelder et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, convection‐permitting models are sensitive to boundary conditions from ESMs (Keller et al., 2018; Shepherd, 2014); thus understanding the mechanisms behind observed changes requires sensitivity analyses, which are still computationally unfeasible. Strategies to exploit the available model runs are thus needed to reach even a minimal level of accuracy for, say, 100‐year events (e.g., Kelder et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…precipitation) such as 100-year events from short (e.g. 30 year) climate model records (Kelder et al, 2020). The UNSEEN trends approach has the potential to detect nonstationarities in a range of climate extremes and can be applied to centurylong seasonal hindcasts (e.g.…”
Section: Pooled Methods For Detecting Changes In Extremesmentioning
confidence: 99%
“…Pooled approaches -both using model ensemble members (e.g. Thompson et al, 2017;Kelder et al, 2020;Massey et al, 2015) and spatial pooling of observations (e.g. Prosdocimi et al, 2019;Blum et al, 2020) -hold considerable promise for enhanced detection and attribution.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…S5 and S6). Furthermore, such a comparison makes it clear that the compared setups are climate model setups and not weather model setups, despite the high spatial resolution (Kelder et al, 2020). While the simulation of individual extremes can differ greatly, the 10-year return levels as a climatic indicator for extreme precipitation show a high degree of agreement (see Fig.…”
Section: Uncertainties Of the Rcm Datasetsmentioning
confidence: 99%
“…Alexandru et al (2007) have shown that a 20-member RCM ensemble of the CRCM driven by the same lateral boundary conditions with slightly perturbed starting conditions leads to a reasonable spread of simulated precipitation. Even seasonal weather model forecast simulations, which are initialized every month, still show variability, especially for precipitation extremes (Kelder et al, 2020;Thompson et al, 2017). Hence, internal variability cannot be excluded as uncertainty source.…”
Section: Uncertainties Of the Rcm Datasetsmentioning
confidence: 99%